Jaypee's Donald School video atlas of ultrasound in fetal anomalies and gynecologic oncology - Kupesic, S. (Sanja)
This video atlas is a step by step guide to ultrasound in foetal anomalies and gynaecologic oncology. It is comprised of two DVDs and numerous high quality 2D, 3D and 4D ultrasound images. With contributions from worldwide experts, this video atlas is an invaluable learning tool for sonographers, radiologists, obstetricians and gynaecologists.